Welcome to the jungle - Ringo, John, 1963-; Moores, Casey (Shadow's path, 2025)
"Dumped in an alleyway as a baby and raised in one of the most vicious inner cities this country has to offer, Michael Edwards' life changed forever when he acquired Earth powers and heard the words, "The Storm is Coming." He trained those powers, forged a team with the other Junior Supers, and took down a vicious criminal. Then, he disappeared to hunt down the remains of that creature's gang on his own. Now, he's back in New York City. Not only is he looking for justice-no, vengeance-for what was done to his mother, but he also seeks the inheritance that's his due. Blocking the path to Michael's inheritance is The Society, a secret organization which runs most of the world and can best be described as pure evil. No teenage boy alive could possibly hope to bring down The Society on his own. Except, perhaps, for one Michael Edwards, aka Stone Tactical, aka Boogie Knight. The Society is about to get a visit, and they won't know what hit them"-- Provided by publisher.